Kajian Yuridis Peraturan Perundang-Undangan yang Baik dan Berkeadilan Bagi Masyarakat - Agustina, Agustina; Purnomo, Sagita (Fakultas Syariah INSURI Ponorogo, 2023)
This study aims to analyze the characteristics of laws and regulations that are good and just for society, to discuss in depth legal remedies against laws that do not fulfill justice for society. This type of research is normative in nature with a descriptive-analytical approach, exploring existing legal symptoms and problems and testing them based on statutory regulations and legal norms. The results of this study indicate that the characteristics of laws that are good and just for the community are regulations that are harmonious, do not overlap with other laws and regulations and their substance accommodates the interests of the community. A good law must have the character of predictability, stability and fairness. Legal remedies against laws whose contents do not satisfy a sense of justice for the people can be carried out through a judicial review to the Constitutional Court, in addition there is also a legislative review, namely periodic reviews by the DPR as legislators as an effort to realize good management of law production.